OpenLand : uma ferramenta livre para análise quantitativa de mudanças de uso e cobertura da terra (UCT) - Exavier, Réginal (2020)
There is an increasing free availability of Land Use and Cover (LUC) time series worldwide. The application of flexible software tools to automate the evaluation of this voluminous data sets are becoming imperative, in order to underpin the understanding of the complex dynamics of anthropized landscapes. Here we present the R package OpenLand, a free and open source tool that automates and optimizes the process of analyzing spatial LUC time series. The structure of OpenLand is divided into three blocks of functionality, for pre-processing, for spatial and non-spatial visualization and one to conduct Intensity Analysis, a methodological procedure, which represents the state-of-the art in quantifying the intensity of LUC changes. The online services Travis CI, AppVeyor and Codecov were used in the development flow to ensure continuous integration of the package, which includes test of coding consistency, the functioning on different computing platforms and its availability at the official and public repository of the Comprehensive R Archive Network (CRAN). Functions, classes and instances created in OpenLand offer a comprehensive and integrated set for automated exploratory analysis of LUC changes in a continuous workflow with sequential processing pipelines. OpenLand is completely documented and written following the best practices for programming with the R language. The functionality of OpenLand is demonstrated using a LUC data set (2002-2014) from the São Lourenço River basin (MT), which is one of the main contribution areas of the northern Pantanal. OpenLand at CRAN, as a free and open source project. Constantely actualized versions are available via GitHub, where the scientific community can contribute in the development, report possible bugs or give suggestions.